2015
DOI: 10.3402/nstep.v1.30103
|View full text |Cite
|
Sign up to set email alerts
|

Towards new forms of educational leadership? The local implementation of förstelärare in Swedish schools

Abstract: In 2013, the Swedish government launched a reform of career services for teachers that introduced fö rstelä rare ('first teacher') as a new category. This article presents results from an ongoing research project about the implementation of the reform in a municipal local context in public schools with attention to leadership practices fö rstelärare engage in and the impact on the educational leadership of the principals. The theoretical framework for the analysis provides perspectives on the interdependencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 23 publications
1
27
0
3
Order By: Relevance
“…'Closing the gap' as a description thus not only apply to the firstteachers in terms of being like brokers between the colleagues and the principal (cf. Alvunger, 2015). A final remark concerning 'gaps' -which however must be examined more thoroughly before any conclusions can be made -is examples of how the VET first-teachers experience an improved relationship between the school and the work places/companies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Closing the gap' as a description thus not only apply to the firstteachers in terms of being like brokers between the colleagues and the principal (cf. Alvunger, 2015). A final remark concerning 'gaps' -which however must be examined more thoroughly before any conclusions can be made -is examples of how the VET first-teachers experience an improved relationship between the school and the work places/companies.…”
Section: Discussionmentioning
confidence: 99%
“…So far we know little of the impact of the CST reform in Sweden because it is so recent, but previous research has shown that first-teachers might strengthen the idea of distributed leadership in schools and at the same time also challenge, to some extent, existing leadership relations and authority -primarily that of the principal (Alvunger, 2015). There are however several international examples of similar reforms.…”
Section: The Cst Reform In Context -Career Services and School Improvmentioning
confidence: 99%
“…There is, however, also research pointing out that teachers in middleleading positions are positive about their assignment and describe themselves as highly motivated, empowered and professionally satisfied with their work (Alvunger 2015;Wenner and Campbell 2017). Recognition strongly contributes to middle-leaders' sense of empowerment and satisfaction, both in the form of monetary compensation (Borchers 2009) and through appreciation shown by colleagues and the principal (see e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing research and evaluations (see, e.g. Alvunger 2015;Öhman et al 2016;SNAE 2014SNAE , 2015 carried out at an early stage of the reform's implementation point to problems such as great uncertainty about the role and tasks of lead teachers, which can be linked to the very novelty of the reform.…”
Section: Contextualising the Present Studymentioning
confidence: 99%
“…Further analyses of relations between advanced teachers and their colleagues reveal legitimate issues caused by the reform as well as the hostile treatment of advanced teachers by colleagues, and the former's resistance to such treatment (Hjalmarsson & Löfdahl Hultman, 2016). Alvunger (2015) discusses how the reform could be seen as a new form of educational leadership, thereby bringing challenges to existing collegial structures and highlighting the need to increase collaboration and interaction.…”
Section: International Trends and Movementsmentioning
confidence: 99%